2021
DOI: 10.3390/ani11123532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Thermal Stress at Later Age on Production Performance and Meat Quality of Fast-Growing, Medium-Growing and Thai Native Chickens

Abstract: The present study aimed at assessing the impact of cyclic thermal stress on production performance and meat quality of commercial broilers (BRs), Thai native chickens (NT) and the hybrids between BR and NT (H75; crossbreed 25% NT). At the age of 3, 5 and 9 weeks for BR, H75 and NT, respectively, each strain was equally divided (n = 50) into control and treatment groups. The controls were raised at a constant 26 ± 1 °C, while the treatments were subjected to thermal stress (35 ± 1 °C, 6 h daily) for 3 weeks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 40 publications
2
19
1
Order By: Relevance
“…Shao et al (2018) demonstrated that cyclic HS (35 °C for 7 days) decreased the BWG, feed intake, and feed/gain ratio of Chinese indigenous broilers (Xueshan broilers). In a study with Thai native chickens, HS exposure also reduced the BWG, but the HS conditions (35 °C for 3 weeks) were not consistent with the current study (Malila et al, 2021). A recent meta-analysis study for fast-growing broilers revealed that the feed intake and feed conversion ratio were not significantly affected by 1-21 days of HS (Andretta et al, 2021).…”
Section: Discussioncontrasting
confidence: 90%
“…Shao et al (2018) demonstrated that cyclic HS (35 °C for 7 days) decreased the BWG, feed intake, and feed/gain ratio of Chinese indigenous broilers (Xueshan broilers). In a study with Thai native chickens, HS exposure also reduced the BWG, but the HS conditions (35 °C for 3 weeks) were not consistent with the current study (Malila et al, 2021). A recent meta-analysis study for fast-growing broilers revealed that the feed intake and feed conversion ratio were not significantly affected by 1-21 days of HS (Andretta et al, 2021).…”
Section: Discussioncontrasting
confidence: 90%
“…An increase in average environmental temperatures has urgently raised global attention as it inevitably impacts the well-being of lives on Earth. For chickens, their physiological response to thermal challenge depends on several factors, including breed, size, and age ( Lu et al, 2007 ; Awad et al, 2020 ; Malila et al, 2021a ). Commercial broilers, meat-type chickens, exhibit more susceptibility to thermal stress than their ancestors ( Tabler et al, 2020 ) and other slow-growing strains ( Washburn et al, 1980 ; Aengwanich, 2007 ; Malila et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…For chickens, their physiological response to thermal challenge depends on several factors, including breed, size, and age ( Lu et al, 2007 ; Awad et al, 2020 ; Malila et al, 2021a ). Commercial broilers, meat-type chickens, exhibit more susceptibility to thermal stress than their ancestors ( Tabler et al, 2020 ) and other slow-growing strains ( Washburn et al, 1980 ; Aengwanich, 2007 ; Malila et al, 2021a ). This has been considered a negative consequence of an artificial breeding selection program focused on production performance and massive mass to meet high consumer demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors affect the incidence of WB including gender, genotype, growth rate, dietary energy, slaughter weight, early dietary restriction and breast yield/size (Kuttappan et al, 2012;Kuttappan et al, 2016). It is known that an environmental temperature above 30C induces heat stress in poultry (Malila et al, 2021;Rajkumar et al, 2021). Consequently, the adverse impact on meat quality via oxidative damage (Reddy et al, 2018) reduces the process of muscle regeneration and the resulting WB (Aslam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%